ANALISIS OBAT KEDALUWARSA, DEAD STOCK DAN OBAT RUSAK DI GUDANG FARMASI RUMAH SAKIT UMUM HIDAYAH PURWOKERTO - Suci Wulan Sari; Desy Arisandi; Okta Mediawati (Jurnal Farmasi IKIFA, 2024)
Drug procurement planning must consider the type and amount of drug needed, because it can cause excess stock and empty stock. The drug storage system in the Hospital Pharmacy Warehouse is very important in maintaining the quality of drugs. An inappropriate storage process can affect the quality of the preparation This research aimed to determine the description and analysis of expired, dead stock and damaged drugs in the Pharmacy Warehouse of Rumah Sakit Umum (RSU) Hidayah Purwokerto. This research used a qualitative descriptive method. The samples used were all expired drugs, damaged drugs and dead stock in the Pharmacy Warehouse of Rumah Sakit Umum Hidayah Purwokerto in the period January-December 2023 using the 0% indicator. In this research, 343 types of drugs were found consisting of expired drugs of 27.11% and dead stock drugs of 3.5%. This is not in accordance with the established indicators, while the percentage of damaged drugs at RSU Hidayah is 0%, this indicates that there is no stock of damaged drugs at RSU Hidayah, so it is in accordance with the established indicators. The causes of these drugs expiring and dead stock are due to a decrease in the number of patients, differences in doctor's prescribing patterns, a slightly drug stock use, so that the drugs pile up and expire.